Works about John Dewey 1886-1995, completed and edited by Barbara Levine, Southern Illinois University Press, Carbondale & Edwardsville 1996, ss. 526 - Brejnak, Hanna (Biuletyn Historii Wychowania, 2003)
Works about John Dewey 1886-1995, completed and edited by Barbara Levine, Southern Illinois University Press, Carbondale & Edwardsville 1996, ss. 526